Preliminary validation of the European Portuguese version of the Robotic Social Attributes Scale (RoSAS) - Oliveira, R.; Arriaga, P.; Stroessner, S.; Paiva, A. (Human Behavior and Emerging Technologies, 2021)
Background: People’s perception of social robots is essential in determining their responses and acceptance of this type of agent. Currently, there are few instruments validated for the European Portuguese population that measures the perception of social robots. Method: Our goal was to translate, validate, and evaluate the psychometric properties of the Robotic Social Attributes Scale (RoSAS) to European Portuguese. To achieve this goal, we conducted a validation study using a sample of 185 participants. We measured the temporal validity of the scale (over a two-week interval) and its divergent and convergent validity using the Portuguese Negative Attitudes towards Robots Scale (PNARS) and the Godspeed scales. Results: Our data analysis resulted in a shortened version of the Portuguese RoSAS with 11 items while retaining the original three-factor structure. The scale presented poor to acceptable levels of temporal reliability. We found a positive correlation between the warmth and competence dimensions. Further validation studies are needed to investigate the psychometric properties of this scale.